Modern techniques to treatment of ceramic surfaces - Omar Abdel Aziz; Ola El Said; Mostafa Abdel Moneim (Journal of Architecture, Art & Humanistic Science, 2018)
This research deals with the techniques of ceramic surface treatment in the stages before firing (biscuits) and some modern and techniques and technical methods in the field of ceramic surface treatment. And the modern techniques such as Agateware, Neriage, Nerikomi and Millefiori and each of these techniques is a type of marbling. The ceramic surface treatment features a wide range of technique and technical characteristics, overlapping and varied, which can help to enrich the ceramic product aesthetically. However, Egyptian ceramic products lack these characteristics and aesthetic values.